PENGARUH KOMPETENSI, PRESTASI KERJA DAN PENGALAMAN KERJA TERHADAP PENGEMBANGAN KARIR KARYAWAN PADA DIVISI ENGINEERING PT. DUMA NUSATAMA BALIKPAPAN - Nainggolan, Hermin; Pardede, Debora Regina (Sekolah Tinggi Ilmu Ekonomi Balikpapan, 2025)
This study aims to determine the effect of competence, work performance, and work experience on employee career development at the engineering division of PT Duma Nusatama Balikpapan. The population of this research is 322 employees of PT.Duma Nusatama Balikpapan. The sample used in this research is purposive sampling which is all permanent employees of Engineering Division of PT Duma Nusatama Balikpapan with 45 respondents. Data analysis technique uses multiple regression method assisted by SPSS 25 program. The result shows that partially competence has positive and significant effect on employee career development with tcount 2.911 > ttable 2.019 and significance value 0.006 < 0.05. Work performance partially has a positive and significant effect on employee career development with tcount 7.774 > ttable 2.019 and a significance value of 0.000 <0.05. Work experience partially has a positive and significant effect on employee career development with tcount 5.334 > ttable 2.019 and a significance value of 0.000 <0.05. Furthermore, competence, work performance, and work experience simultaneously have a significant effect on the career development of engineering division employees with a value of Fcount 306.486 > Ftable 2.83 and a significance value of 0.000 <0.05